2011
DOI: 10.1093/carcin/bgr181
|View full text |Cite
|
Sign up to set email alerts
|

Selective changes of retroelement expression in human prostate cancer

Abstract: Retroelements constitute a large part of the human genome. These sequences are mostly silenced in normal cells, but genome-wide DNA hypomethylation in cancers might lead to their re-expression. Whether this re-expression really occurs in human cancers is largely unkown. We therefore investigated expression and DNA methylation of several classes of retroelements in human prostate cancer tissues and cell lines by quantitative reverse transcription-polymerase chain reaction and pyrosequencing, respectively. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 48 publications
11
100
0
Order By: Relevance
“…It is not clear whether the HERV-K 5 0 LTR region alone is sufficient to activate EVT1 expression in these patients. However, our results suggest that the 5 0 LTR promoter region from HERV-K not only is active but can also increase expression in response to androgen hormone stimulation, in accordance with previous findings (37). Taken together, these findings highlight the importance of HERV-K activity in prostate cancer.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is not clear whether the HERV-K 5 0 LTR region alone is sufficient to activate EVT1 expression in these patients. However, our results suggest that the 5 0 LTR promoter region from HERV-K not only is active but can also increase expression in response to androgen hormone stimulation, in accordance with previous findings (37). Taken together, these findings highlight the importance of HERV-K activity in prostate cancer.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that the DNA methylation status of the HERV-K promoter region (LTR) contributes to GAG-HERV-K expression in cancer cell lines. In accordance with our findings, HERV-K from chromosome 22q11.23 was recently observed to be highly expressed in prostate cancer samples and the expression was dependent on LTR region demethylation (37). Nevertheless, methylation is just one of several mechanisms that impact chromatin structure and gene expression, and it is possible that some of the heterogeneity in GAG-HERV-K expression observed among cancer cell lines may relate to differences in other possible pathways (acetylation, etc.)…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[45][46][47][48] In particular, the detection of RNA transcripts of HERVs was described in various human tissues and cancer cells. 49,50 LTRs are usually oriented opposite to the transcription direction of the corresponding host genes and the antisense transcripts affect the partner gene functions, by modifying both the transcriptional and posttranscriptional regulation processes. [51][52][53][54][55][56][57][58] LTRs may also promote cellular transformation by cis activation of downstream oncogenes, and the repetitive nature of HERVs provides an ideal substrate for nonallelic homologous DNA recombination, which results in a variety of germline chromosomal rearrangements, leading to human genetic disorders and cellular transformation of somatic cells.…”
Section: Hervs and Oncogenic Mechanisms: The Negative Sidementioning
confidence: 99%